2019
DOI: 10.1002/dys.1644
|View full text |Cite
|
Sign up to set email alerts
|

Preschool teachers' language and vocabulary knowledge: Development and predictive associations for a new measure

Abstract: The present study reports on the development, structure, and associations with practice for a new measure of preschool teachers' knowledge about language and vocabulary development and how to support this development in the classroom. Results from item response theory models with responses from a sample of 248 preschool teachers indicated that four scales measuring pedagogical content knowledge and content knowledge for vocabulary and language, respectively, had adequate psychometric characteristics. Confirmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…In our work, by defining engagement as the active behaviors children may perform to show evidence of their ability to participate in and learn from the instructional context created by adults, we see an opportunity to elevate the importance of each adult in the classroom taking an active role in facilitating meaningful learning opportunities for each child within a classroom. Future research that examines this premise and extends findings of other researchers exploring how different adults within educational teams contribute to the frequency (Phillips et al, 2020), as well as quality and form (Kook & Greenfield, 2020), of adult–child interactions is necessary to create actionable knowledge on a pathway to improved outcomes for children.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In our work, by defining engagement as the active behaviors children may perform to show evidence of their ability to participate in and learn from the instructional context created by adults, we see an opportunity to elevate the importance of each adult in the classroom taking an active role in facilitating meaningful learning opportunities for each child within a classroom. Future research that examines this premise and extends findings of other researchers exploring how different adults within educational teams contribute to the frequency (Phillips et al, 2020), as well as quality and form (Kook & Greenfield, 2020), of adult–child interactions is necessary to create actionable knowledge on a pathway to improved outcomes for children.…”
Section: Discussionmentioning
confidence: 77%
“…In exploring the causal pathway presented in Figure 1 (top panel), we first conceptualize cognitive factors, such as the classroom pedagogy or predominant instructional philosophy, which may influence educator teams as they make decisions about how to arrange their instruction and what specific practices to use as part of a learning process (Phillips et al, 2020). Those decisions manifest in the observable forms that learning opportunities take as a mechanism for promoting children’s engagement.…”
Section: Exploring a Pathway To Enhancing Engagement And Improving Outcomesmentioning
confidence: 99%
“…Much is inferred, for example, in studies of professional development which aim to improve knowledge and have subsequently identified effects on practice (Dickinson & Caswell, 2007;Wasik, Bond & Hindman, 2006). Studies which explicitly assess pedagogical language-andliteracy knowledge have identified small or null effects (Piasta, Park, Farley, Justice & O'Connell, 2020;Phillips, Oliver, Tabulda, Wood & Funari, 2020;Spear et al, 2018;Schachter et al, 2016). Such equivocality is puzzling, given the theoretical value of domain-specific pedagogical knowledge and evidence of its importance in later education phases, for example, in the domain of mathematics teaching (Baumert et al, 2010;McCray, 2008).…”
Section: The Role Of Teacher Knowledge and The Limits Of Current Resementioning
confidence: 99%
“…There is empirical evidence that pre-school teachers language-and-literacy content knowledge predicts classroom quality and child outcomes (Piasta et al, 2009;Schachter et al, 2016). However, equivalent evidence does not exist for pedagogical knowledge: studies are scarcer and have identified small or null effects (Phillips et al, 2020;Spear et al, 2018;Schachter et al, 2016). This is puzzling, given evidence from later educational phases that pedagogical knowledge does matter (Baumert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%